Building a model of artillery firing efficiency under conditions of limited ammunition resources and barrel wear - Maksymov, Maksym; Boltenkov, Viktor; Dobrynin, Yevhenii; Sidelnykov, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2025)
This study examines the process of destroying individual and group targets by an artillery battery under conditions of limited ammunition of a given quality and varying degrees of barrel bore wear. The task addressed relates to the revealed lack of a quantitative model that would make it possible to assess the effectiveness of aimed or planar fire in the presence of resource limitations on shots and barrel bore wear, which could facilitate determining the threshold conditions for the feasibility of continuing fire. A discrete stochastic model of the effectiveness of firing an artillery unit has been proposed. The model is designed to assess the effectiveness of aimed fire under conditions of limited resource of high-quality ammunition. The model also takes into account the presence of guns in the unit, the barrels of which have different levels of wear. It is proposed to divide shots from each gun in the artillery unit into four different classes, which takes into account the quality of the shot elements: the projectile and the propellant charge, as well as the condition of the barrel. It is proposed to consider the successive states of the artillery unit's guns as elements of the Markov chain. It was established that it is possible to achieve a firing efficiency coefficient that lies within the range of 0.63−0.83. The limiting estimate of the firing efficiency coefficient of the artillery unit on a separate target was obtained, which is equal to 0.5. The results showed that when the limiting value of the firing efficiency coefficient is obtained, aimed fire degenerates into planar target destruction with enlarged scattering ellipses. This state leads to an almost twofold increase in the cost of shots and the time of firing, which sharply increases the risk of counter-battery damage to the battery. Such results are attributed to the combination of the accepted classification of shots by quality, taking into account the increased wear of the barrel bores due to a decrease in the probability of hitting, and the analysis of a set of realistic gun firing strategies. The model could be offered for performing tactical calculations when choosing a fire mode, the structure of using available ammunition, and assessing the feasibility of switching from aimed to plane fire